La Casa de Carlota: A Studio Where the Diversity Wins. (October 2019) - Magomedova, Nina; Bastida-Vialcanet, Ramon
This case is based on La Casa de Carlota (Carlota's House), a limited liability company founded in 2013 and located in Barcelona. The company integrates a design studio and a professional communication agency and employs people with Down's syndrome or autism. This case features the decision process followed by the two cofounders, José Maria Batalla and Sergi Capell, regarding the opportunity of growing, by either scaling up the activity of the company or replicating the model in other countries. The case describes the concerns that the entrepreneurs had to face in order to make a decision, such as the choice of funding sources in order to finance the growth, or the issues related to the hiring and managing of people with Down's syndrome or autism. The case also describes the background of the entrepreneurs, the start-up, and the industry. The case introduces the students to the social entrepreneurship field and explains a business model that generates an important social impact. It also introduces a topic of start-ups' scaling and growth, and different alternatives for financing them. The case sheds light on critical questions that social entrepreneurship students, scholars, investors, and authorities often pose.